2011
DOI: 10.1111/j.1365-2591.2011.01984.x
|View full text |Cite
|
Sign up to set email alerts
|

A maxillary lateral incisor with four root canals

Abstract: • Clinicians should be aware of the variable root canal anatomy in maxillary lateral incisor teeth. • Careful examination of radiographs and the internal anatomy of teeth are essential prerequisites for successful root canal treatment. • Four root canals in maxillary lateral incisors is a possibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…The literature shows that MLI with a maximum of four canals has been reported,[4] but as far as the author's knowledge, this is the first case with FRC, especially in a peg-shaped lateral incisor complicated by the presence of DI. According to the literature, DI in a MLI is considered as unusual.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The literature shows that MLI with a maximum of four canals has been reported,[4] but as far as the author's knowledge, this is the first case with FRC, especially in a peg-shaped lateral incisor complicated by the presence of DI. According to the literature, DI in a MLI is considered as unusual.…”
Section: Discussionmentioning
confidence: 94%
“…Considering the occurrence of additional canals, the literature shows that, MLI with a maximum of four canals[4] and with dens formation, three root canals[5] have been reported. Zillich et al .…”
Section: Introductionmentioning
confidence: 99%
“…Independent studies consistently report that maxillary lateral incisors have single root canals 1,8. However, there are reports of maxillary lateral incisors with two or three canals 2,3,9,10. These are thought to be the result of abnormal development of the tooth and root.…”
Section: Discussionmentioning
confidence: 99%
“…Vertucci has reported that maxillary incisors present a single root and single canal. However, numerous case reports have shown two, [7,8] three, [5] and even four [9,10] canals. Clinically, maxillary lateral incisors with anatomic variations often indicate a fusion, [11] gemination, [12] dens invaginatus, [10] or a palatogingival groove.…”
Section: Discussionmentioning
confidence: 99%
“…[15,16] Therefore, cone beam computed tomography was used as a diagnostic tool by many authors for evaluating extra canals or roots. [9] In this case, CBCT scanning was used for three-dimensional analysis of the root canal system with detection of the location of roots. Buccal and palatinal canals were not clearly detectable on conventional radiographs because of superimposition.…”
Section: Discussionmentioning
confidence: 99%